In Silico and in Vitro Evaluation of Real Time PCR Assay for Detection of Staphylococcus aureus - AL-Rawi, Al-Shaimaa Muhammed Saeed; AlKazaz, Abdul Kareem A; Sabbah, Majeed Arsheed; Al-Zubaidi, Mohammed Mahdi (Al-Nahrain Journal of Science, 2017)
Many research groups developed real time PCR assays for identification of Methicillin-resistant Staphylococcus aureus (MRSA). They designed different primers and probes in their assays. Gene mecA is the target identification of MRSA by PCR assay. The aim of this study is using in silico approach to identify the best primers and probe for real time PCR identification mecA gene. Published primers and probes were analyzed in silico to select the best for real time PCR identification of mecA gene. The selected primers and probe successfully used for real time amplification of twenty MRSA tested. This study reveals the importance of in silico approach for designing diagnostic assays shorten the cost and the time.